2021
DOI: 10.1016/j.apsb.2021.06.017
|View full text |Cite
|
Sign up to set email alerts
|

TRIB3‒GSK-3β interaction promotes lung fibrosis and serves as a potential therapeutic target

Abstract: Pulmonary fibrosis (PF) is a chronic, progressive, fatal interstitial lung disease with limited available therapeutic strategies. We recently reported that the protein kinase glycogen synthase kinase-3 β (GSK-3 β ) interacts with and inactivates the ubiquitin-editing enzyme A20 to suppress the degradation of the transcription factor CCAAT/enhancer-binding protein beta (C/EBP β ) in alveolar macrophages (AMs), resulting in a profibrotic phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…Accumulating evidence has widely demonstrated that TRIB3 plays a vital role in organ fibrogenesis ( Wang et al, 2014 ; Tomcik et al, 2016 ; Zhang et al, 2020 ). Our previous study, along with others, reported the key role of TRIB3 in promoting PF ( Yu W. et al, 2019 ; Liu S. et al, 2021 ). We found that TRIB3 was substantially upregulated in alveolar macrophages (AMs) from patients with PF, inducing the profibrotic phenotype of AMs.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Accumulating evidence has widely demonstrated that TRIB3 plays a vital role in organ fibrogenesis ( Wang et al, 2014 ; Tomcik et al, 2016 ; Zhang et al, 2020 ). Our previous study, along with others, reported the key role of TRIB3 in promoting PF ( Yu W. et al, 2019 ; Liu S. et al, 2021 ). We found that TRIB3 was substantially upregulated in alveolar macrophages (AMs) from patients with PF, inducing the profibrotic phenotype of AMs.…”
Section: Discussionsupporting
confidence: 55%
“…These data indicated that the decreased protein expression of TRAF6 in lung fibroblasts during PF progression might result from an alteration in its protein stability. Our group, along with others, has reported that TRIB3, a well-known stress sensor, is involved in regulating the stability of various proteins in the pathogenesis of chronic diseases ( Lin et al, 2019 ; Yu J. M. et al, 2019 ; Liu S. et al, 2021 ). We then reasoned that TRIB3 might participate in regulating the altered protein expression of TRAF6.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Recent studies have shown that C/EBP β deficiency results in a complete lack of segregated nucleus-containing atypical monocytes (Ly6C − F4/80 − Mac1 + Ceacam1 + Msr1 + ) derived from Ly6C − Fc ε RI + granulocyte/macrophage progenitors, preventing the development of bleomycin-induced lung fibrosis [ 190 ]. Moreover, high C/EBP β levels in monocyte-derived alveolar macrophages, but not tissue-resident alveolar macrophages, promotes lung fibrosis [ 42 , 214 ]. During lung injury, the stress response protein Trib3 in monocyte-derived alveolar macrophages interacts with GSK-3 β and protects it from ubiquitination and degradation [ 214 ].…”
Section: Roles Of C/ebps In the Fibrotic Processmentioning
confidence: 99%
“…Pulmonary fibrosis is the end-stage outcome of a large variety of lung diseases characterized by excessive fibroblast proliferation, aberrant extracellular matrix (ECM) deposition with inflammatory injury, and destruction of tissue structure 1 . The most common disease type is idiopathic pulmonary fibrosis (IPF), a severe interstitial lung disease that leads to progressive loss of lung function, resulting in significant medical burden due to its severe clinical manifestations, poor prognosis, and high mortality 2 .…”
Section: Introductionmentioning
confidence: 99%